a The Relationship Between Health Professionals' Interprofessional Competence and the Speed of Action in Acute Emergency Situations: The Relationship Between Health Professionals' Interprofessional Competence and the Speed of Action in Acute Emergency Situations - Darmawan, Rezky (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
The Relationship Between Health Professionals' Interprofessional Competence and the Speed of Action in Acute Emergency Situations